2020
DOI: 10.3390/ijms21207535
|View full text |Cite
|
Sign up to set email alerts
|

Constant Light Dysregulates Cochlear Circadian Clock and Exacerbates Noise-Induced Hearing Loss

Abstract: Noise-induced hearing loss is one of the major causes of acquired sensorineural hearing loss in modern society. While people with excessive exposure to noise are frequently the population with a lifestyle of irregular circadian rhythms, the effects of circadian dysregulation on the auditory system are still little known. Here, we disturbed the circadian clock in the cochlea of male CBA/CaJ mice by constant light (LL) or constant dark. LL significantly repressed circadian rhythmicity of circadian clock genes Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…In the current study, innate immune response assessed as Iba1 + cell counts within the sensory epithelium at 7 dpn was not exacerbated, and instead was reduced, despite auditory physiological deficits in f/f cKO GR mice. Noise–dose divergent cochlear immune response was also found in investigations of circulating Cort related to circadian rhythm state, patterning levels of noise-induced damage with auditory physiology [ 20 , 99 , 100 ]. Some distinctions about the influence of GR expressed in supporting cells may be made: (1) supporting cell GR knockdown (f/+ heterozygous cKO GR), which could represent circadian time (based on available open receptors) distinct from control (no tamoxifen) mice, had typical physiological recovery from noise exposure and (2) supporting cell GR ablation was detrimental to auditory physiological recovery from noise exposure.…”
Section: Discussionmentioning
confidence: 92%
“…In the current study, innate immune response assessed as Iba1 + cell counts within the sensory epithelium at 7 dpn was not exacerbated, and instead was reduced, despite auditory physiological deficits in f/f cKO GR mice. Noise–dose divergent cochlear immune response was also found in investigations of circulating Cort related to circadian rhythm state, patterning levels of noise-induced damage with auditory physiology [ 20 , 99 , 100 ]. Some distinctions about the influence of GR expressed in supporting cells may be made: (1) supporting cell GR knockdown (f/+ heterozygous cKO GR), which could represent circadian time (based on available open receptors) distinct from control (no tamoxifen) mice, had typical physiological recovery from noise exposure and (2) supporting cell GR ablation was detrimental to auditory physiological recovery from noise exposure.…”
Section: Discussionmentioning
confidence: 92%
“…Here, we screened the optimal condition of SC by exposing animals to 8–16 kHz octave‐band at different intensities for 2 h. 80, 90, and 106 dB SPL were selected as low, moderate, and high intensity of noise exposures. In the previous literature, 2 h of 106 dB SPL 8–16 kHz noise exposure has been commonly used to induce permanent hearing loss 27–29 . We first examined the auditory thresholds 1 and 14 days after sound exposure of various intensities.…”
Section: Resultsmentioning
confidence: 99%
“…Dysregulated circadian rhythms may affect the cellular antioxidant system and link to oxidative stress 53 . We have recently reported that constant light dysregulated the cochlear circadian clock, augmented the production of reactive oxygen species, and increased the threshold shift of mice exposed to high‐intensity noise 12 . Therefore, it was reasonable to postulate that the repeated triggers in MD disrupt the circadian clock, followed by increasing the oxidative stress in the inner ear and eventually deteriorate the hearing in MD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the central pacemaker, peripheral organs including liver, heart, kidney, and peripheral blood (PB) leukocytes also contain circadian oscillators, 9 which are the networks that generate 24‐h rhythms in each organ 10 . Cochlea 11,12 and inferior colliculus 13 also have the circadian clock in the experimental animal models. At least nine core circadian clock genes ( PER1 , PER2 , PER3 , CRY1 , CRY2 , CLOCK , CK1ε , BMAL1 , and TIM ) regulate central and peripheral circadian oscillators in transcriptional‐translational feedback loops 8 .…”
Section: Introductionmentioning
confidence: 99%